Organic carbon accumulation in coastal zones since the last glacial maximum? A clue for varying atmospheric CO2 levels? - Boski, T. (2013)
It is a generally accepted concept that the carbon storage within the principal earth surface reservoirs varies in a multitude of time scales. The shallow water continental margins belong to the most fertile areas in terms of organic carbon (OC) production and are also very effective carbon traps.